Pregnancy Outcomes in Maternal Neuropsychiatric Illness and Substance Abuse - Bartel, Severine; Costa, Serban Dan; Kropf, Siegfried; Redlich, Anke; Rissmann, Anke (Geburtshilfe und Frauenheilkunde, 2017)
Introduction Worldwide the prevalence of neuropsychiatric illness among women of reproductive age is higher than ever before. This study investigates the influences of maternal substance abuse/dependence and neuropsychiatric illness on pregnancy and neonatal outcomes.Patients and Methods Using a retrospective study design 185 pregnancies in women with neuropsychiatric illnesses or substance abuse were identified at a single centre over a period of 3.25 years and compared to 4907 pregnancies in healthy women without mental illness. Differences in pre-, peri- and postnatal pregnancy parameters were studied.Results Numbers of previous abortions on obstetric history were significantly higher in cases compared to controls, women with depression being especially affected. The number of antenatal visits was also higher among cases, especially in women with depression. The caesarean section rate was significantly higher in cases compared to controls. Children of women with neuropsychiatric illness were born at lower gestational ages than those of healthy control mothers, however there were no significant differences between case and control groups for birth weight, head circumference or Apgar scores. Some isolated differences were found for disease-specific case subgroups compared to controls.Conclusion The study shows a relationship between maternal neuropsychiatric illness and pregnancy outcomes independent of medication use. Rates of spontaneous abortion were higher. Children were born earlier, yet the neonatal outcomes birth weight, head circumference and Apgar score were not worse than children of mentally healthy women.Einleitung Unter Frauen im gebärfähigen Alter ist die Prävalenz neuropsychiatrischer Erkrankungen weltweit so hoch wie nie. Die Studie geht der Frage nach, welchen Einfluss die mütterliche Suchterkrankung oder neuropsychiatrische Erkrankung auf den Schwangerschaftsausgang und auf das neonatale Outcome hat.Patienten und Methoden In einer monozentrischen, retrospektiven Studie konnten über einen Zeitraum von 3,25 Jahren 185 Schwangerschaften von Frauen mit neuropsychiatrischer Erkrankung oder Suchterkrankung identifiziert werden und 4907 Schwangerschaften von mental gesunden Frauen gegenübergestellt werden. Es wurden Unterschiede im prä-, peri- und postpartalen Schwangerschaftsverlauf untersucht.Ergebnisse Die Anzahl an anamnestischen Aborten war in der Fallgruppe signifikant höher als in der Kontrollgruppe. Vor allem Frauen mit Depression waren davon betroffen. Auch die Anzahl an Vorsorgeuntersuchungen während der Schwangerschaft war in der Fallgruppe vor allem durch Frauen mit Depression erhöht. Die Sectiorate der Fallgruppe war gegenüber der Kontrollgruppe signifikant erhöht. Die Kinder neuropsychiatrisch erkrankter Frauen sind früher zur Welt gekommen als Kinder der Kontrollmütter. Sie hatten jedoch im Vergleich von Fall- und Kontrollgruppe kein signifikant niedrigeres Geburtsgewicht, keinen kleineren Kopfumfang oder schlechtere APGAR-Werte. Im Vergleich einzelner krankheitsspezifischer Untergruppen zur Kontrollgruppe lagen vereinzelt Unterschiede vor.Fazit Es konnte ein Zusammenhang zwischen neuropsychiatrischer Erkrankung der Mutter und dem Schwangerschaftsausgang, unabhängig von der Medikation, nachgewiesen werden. Die Rate an Spontanaborten war höher. Die Kinder kamen früher zur Welt, jedoch war das Outcome der Kinder in Bezug auf Geburtsgewicht, Kopfumfang und APGAR-Werten nicht wesentlich schlechter als das von Kindern neuropsychiatrisch gesunder Frauen.
Keywords: pregnancy outcome; neuropsychiatric illness; abortion; fetal outcome; pregnancy